Pengembangan Media Pembelajaran Interaktif Berbantuan Lectora Inspire dan Plotagon pada Materi Operasi Aljabar - Diah Novita Wiji Utami (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The utilization of learning media has an impact on the achievement of students' abilities in learning. The use of interactive learning media can support students in achieving learning objectives. Students can interact with learning media anywhere and anytime as well as interact with teachers. The purpose of this research is to produce interactive learning media on algebraic operation material that can be used on computers. The product produced in this study is an interactive learning media that has an attractive illustration presentation containing material explanations, problems and solution steps to guide students in the learning process. This type of research uses R&D (Research and Development) with the ADDIE development model. The ADDIE development model consists of 5 main stages, namely analysis, design, development, implementation, and evaluation. The research was conducted at SMPN 2 Maesan with the research subject being 32 students of class VII A. The results of the development of interactive learning media were tested valid, effective, and practical. Valid is indicated by the total average value of 3.93 and the correlation coefficient value of 0.98 so that it is included in the valid category. Effective is indicated by the N-Gain value of 0.57 with a percentage of completeness of 87.5% of the total 32 students, so this media is effective in improving student learning outcomes. Practical is indicated by a total average value of 3.418 and a percentage of the results of the questionnaire.
Reaploud Repository February 2026_Hasyim
Keywords: learning media; interactive; algebraic operations.